Maintaining autonomy: How older persons with chronic conditions and their significant others interpret, navigate, and overcome everyday difficulties - Thomas Ballmer; Brigitte Gantschnig (Scandinavian Journal of Occupational Therapy)
Background The vast majority of older adults live in their own homes. Many of them live with chronic conditions that lead to activity limitations and participation restrictions. To support them adequately, we need to better understand how they cope with everyday difficulties.Aim To identify and examine difficulties in everyday life older people with chronic conditions who live in private homes face and how they and their significant others interpret, navigate, and overcome these difficulties.Material and Methods We conducted a focus group interview with 10 participants including eight older adults with chronic conditions and two of their significant others. We then transcribed the interviews verbatim and thematically analysed them.Results We generated the three closely interrelated themes struggling not to lose control, a shifting balance between resources and environmental challenges, and negotiating independence and interdependence. Participants interpreted the difficulties they faced as multicausal. Their main goal was maintaining autonomy, agency, and a positive identity. They employed individual, creative strategies to achieve these goals.Conclusions Older persons with chronic conditions prioritise autonomy and agency in order to maintain a positive identity.Significance Interventions to support older persons with chronic conditions should centre their priorities and build on their creativity.